The Relationship among Spiritual Intelligence, Emotional Intelligence, Organizational Citizenship Behaviour, and Employee Performance - Achmad Sani Supriyanto; Vivin Maharani Ekowati; Masyhuri Masyhuri (ETIKONOMI, 2019)
The effect of Intelligence on employee performance is highly essential, although contradictions related to the current research found. This research aims to analyze the direct and indirect effect of spiritual intelligence and emotional intelligence on employee performance through Organizational Citizenship Behavior (OCB). This research using Partial Least Square (PLS) with 50 respondents as samples. It shows that emotional intelligence has a direct and indirect effect on employee performance. Meanwhile, spiritual intelligence only has a direct effect on employee performance. Emotional intelligence can increase employee performance indirectly through OCB. Management implies that the supervisor is supposed to conduct an assessment on OCB to enhance employee performance continuously.JEL Classification: D23, J24